Fibrinogen-to-albumin ratio (FAR) is the best biomarker for the overall survival of patients with non-small-cell lung cancer - Ma, Shixin; Wang, Lunqing (Frontiers in Oncology, 2024)
Objective: Inflammatory response and nutritional status are associated with overall survival (OS) in patients with non-small cell lung cancer (NSCLC), but it is unclear which biomarkers are better suited to predict their prognosis. This study sought to determine which of the common existing inflammatory and nutritional indicators best predicted the OS.The study included 15 compound indicators based on inflammation or nutrition, with cutoff points obtained through the receiver operating characteristic curve (ROC). Univariate and multivariate Cox proportional risk models were used to evaluate the relationship between predictors and OS. Kaplan-Meier curves were used for survival analysis, and log-rank tests were used to compare differences between groups. The C-index is calculated to evaluate the predictive ability of different indicators.The study included 899 patients with NSCLC. In univariate analysis, all 15 measures were significantly associated with patients' OS (all P<0.05). C index analysis results show that FAR, SII, and AAPR are the three indexes with the best predictive performance. Among them, FAR (C index: 0.639) had the best predictive power for OS in NSCLC patients. In different subgroups, FAR had the highest C index in male, non-smoking, adenocarcinoma, and stage II patients. The C-index of PLR in female patients was the highest. SII was highest in smokers, age <65 years and ≥65 years, and stage III patients; the C index of AAPR was the highest in non-adenocarcinoma. The C index of PIV was highest in stage I patients. In multivariate Cox regression analysis, among FAR, SII, and AAPR, only FAR was an independent predictor of OS in NSCLC patients. High FAR was associated with a higher risk of death in patients with NSCLC [HR, 1.601; 95%CI,]. In order to further evaluate the potential prognostic value of FAR, SII, and AAPR in patients with different stages, Cox regression analysis was performed for patients with stage I-II and stage III NSCLC, respectively, and the results showed that FAR was an independent prognostic factor for OS in patients with stage I-II NSCLC.For all NSCLC patients, the prognostic power of FAR is superior to other inflammatory and nutritional indicators.